LATIHAN BINA DIRI PADA SISWA TUNAGRAHITA DALAM MENINGKATKAN KEMANDIRIAN - Aep Kusnawan; Sitta Resmiati Muslimah; Ajrina Amalia S. (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2022)
This study was intended to determine the process and results of self-development exercises in increasing the independence of mentally retarded students. The object of the research is mentally retarded students at SLB BC YPLAB Wartawan, Bandung City. The research method used is a qualitative descriptive method in which to obtain information the researcher uses observation, interview, and documentation techniques. The results showed that self-development exercises at SLB BC YPLAB Journalists were effective. This happened thanks to a special schedule and made it a special mandatory program for mentally retarded students, the implementation also uses various methods, so that the results can increase the independence of mentally retarded students positively